Assesment of gait disturbances in hemiparetic patients with and without AFO by pedobarographic measurements [Hemėparetėklerde AFO'lu ve afo'suz yürüme bozukluklarinin pedobarografi̇k ölçümler i̇le deǧerlendi̇ri̇lmesi̇] - (:unkn) unknown (My University, 2005)
To achieve independent gait is one of the main goals of rehabilitation after stroke. The purpose of this study was to evaluate walking velocity, initial contact, pressure changes in stance phase by pedobarographic measurement and to assess changes of these parameters with using ankle foot orthosis (AFO) in hemiparetic patients with dynamic equinovarus deformity. Fifteen hemiparetic patients were included in the study. Solid AFO were made for patients to improve their gait patterns. Ankle spasticity and daily living activity were assessed with Modified Ashworth Scale and Barthel Index, respectively. In addition, 10 m walking time was evaluated with and without AFO, and dynamic pedobarographic measurements were used to determine the pressure changes on the foot during walking. The mean 10 m walking time with AFO and without AFO were 17.2±4.2 s and 19.2±4.3 s, respectively. The stance time in the affected side was significantly more than the one in the unaffected side, in both with AFO and without AFO (p<0.05). However, the difference in the affected side stance time with AFO and without AFO was not significant (p<0,05). 10 m walking time and the loading pressure with AFO were significantly different than those were walking without AFO (p<0,05). According to the patient global assessment, they have expressed more comfortable and safe walking with AFO than walking without AFO. Based on our findings, we conclude that in hemiparetic subjects with dynamic equinus deformity, using an solid AFO improves initial contact during the stance phase and prevents drop foot during the swing phase and hence it provides reliable and rapid walking.
Keywords: AFO; Hemiplegia; Pedobarographic measurement; Stroke